Food sovereignty, food practices and territorial conflict in the Quilombola community Angelim I - Sapê do Norte (ES) - Leão Ponce Pasini, Isabela (Geografares, 2018)
This article presents reflections about the relationship between food sovereignty, food practices and territory in the quilombola community Angelim I, in the “Sapê do Norte” region, state of Espírito Santo, based on part of the author’s master’s research, carried out as a case study. Ours perspective comes from the Geography glance mainly, with food as the central axis to unveil, through literature review, field research, oral history and participatory mapping with the inhabitants, the changes in food practices and their territorialities upon arrival of companies, the implications in their way of life, thus pointing out the difficulties and r-existences of the community. Keywords: foods overeignty, food practices, quilombola territoriality.